INCREASING STUDENTS VOCABULARY BY USING MIND MAPPING TECHNIQUE AT SMP N 2 BITUNG - Delatu, Tara A.; Wowor, Diane; Kamagi, Sarah (English Education Department, 2020)
The purpose of the study was to find out whether using mind mapping technique can increase students vocabulary or not It was conducted at SMP N 2 Bitung The subject in this study was Class V11 4 academic year 2017 2018 which consisted of 35 students This research was a pre experimental design with one group pre test post test Pre test is the test which was given to the students before treatment to find out students vocabulary stock Post test is the test which was given to the students to find out the students achievement after treatment or teaching them by using mind mapping technique The findings showed that the students score in post test were higher than the pre test The result of the data analysis revealed that the mean score of post test 82 was higher than the pre test 49 In addition the standard deviation of pre test was slightly higher 7 05 than the standard deviation of post test 5 71 This indicated that the use of mind mapping technique increased students vocabulary < p>